Enhancing Administrative Literacy and Bookkeeping Management in Urban Farming as a Contextual Learning Model for Prospective Elementary School Teachers - Erni Suharini; Ervando Tommy Al-Hanif; Edi Kurniawan; Satya Budi Nugraha; Nasir Nayan; Nasir Nayan (EduStream: Jurnal Pendidikan Dasar, 2025)
This research seeks to strengthen administrative literacy and bookkeeping management within urban farming as a form of contextual learning for future elementary school teachers. The project evolved from a community engagement initiative conducted in Sampangan Village, Semarang City, with the Women Farmers Group (Kelompok Wanita Tani) Puspitasari serving as a case model for promoting food security through urban agriculture. A participatory training method was applied, involving lectures, group discussions, practical demonstrations, and guided mentoring. Data were obtained through pre- and post-training questionnaires and analyzed using descriptive statistics alongside paired sample t-tests. The findings indicated a notable enhancement in participants’ administrative and bookkeeping competencies, with the mean score rising from 65.15% (moderate) prior to the training to 82.70% (high) afterward. These results highlight that administrative literacy supported by systematic bookkeeping can function as an effective contextual learning framework for preservice elementary teachers by combining authentic problem-solving, environmental consciousness, and managerial abilities. Moreover, urban farming activities not only advance ecological awareness but also nurture critical thinking, collaboration, and entrepreneurial skills consistent with the Merdeka Belajar curriculum in primary teacher education. This approach presents a replicable model for teacher education programs seeking to integrate social, ecological, and managerial literacies into sustainable community-based learning. Furthermore, it offers practical guidance for embedding contextual, project-based experiences into preservice teacher curricula to strengthen professional readiness and community engagement.